Earth-based mortars for repair and protection of rammed earth walls. Stabilization with mineral binders and fibers - Gomes, Maria (2018)
The use of earth as a building material offers many advantages in terms of sustainability: it is a natural material, most probably non-toxic and ecological, with low energy intensity, low carbon emissions and recyclable. Earth-based mortars are re-gaining its place as building materials for plastering, rendering and repair of earthen walls, not only in the sustainable context but also in terms of efficiency. However, the scientific knowledge about these mortars is still scarce. In particular, the opinions regarding the effects of adding fibers or mineral binders as stabilizers, to improve the performance of the mortar, are contradictory. The study presented in this article is intended to advance the knowledge about the effects of adding low amounts of hemp fibers, hydrated air lime, hydraulic lime, natural cement and Portland cement on the mechanical (flexural and compressive strength, dynamic modulus of elasticity), physical (shrinkage, thermal conductivity, porosity) and hydric (water absorption under low pressure, capillary water absorption, drying) characteristics of mortars formulated with different earth materials. Results show that the addition of the fibers decreases the thermal conductivity of the mortars, which is remarkably good for the mortars made from clayey soil, and slowers the drying of the mortars. They also show that adding the mineral binders will negatively affect the hydric behaviour of the mortars: the water absorption coefficient increases and the drying become slower as the percentage of binder increases. In addition, the use of these binders has no significant effect on the flexural and compressive strength of the mortar.